Development of Competency Testing Tools for IIoT-Based Pneumatic Control System Operation Clusters Using Siemens S71200 PLC and Node-Red - Lutfi, Lutfi; Muchtar, Taufik; Tri Budi Utami, Atikah (UPPM Poltek ATI Makassar, 2024)
The Polytechnic ATI Makassar emphasizes the importance of producing D3 graduates who meet industry needs through the Professional Certification Institute (LSP), which has developed 42 certification schemes for various study programs, including Mechanical System Automation. One prominent scheme is the Pneumatic Control System Operation Cluster, which refers to Indonesia's national competency standards in the processing industry. The ultimate goal is to prepare graduates to design Industrial Automation Systems, in line with the Making Indonesia 4.0 initiative. This research aims to develop a competency test tool based on IIoT, upgrading technology from conventional pneumatics to an electro-pneumatic system using PLC and a web-based HMI user interface using Node-Red. The research adopts a Research and Development (RnD) methodology with the DEDTE (Define, Explore, Design, Test, Evaluate) approach. The case studied is a Material Handling System using two cylinders with a sequence of A+ B+ A- B-, involving 16 I/O tags for the PLC. The initial state diagram design resulted in four states, which were then converted into five networks in the form of ladder diagrams. Kepware OPC Server was used to connect PLC tags to Node-Red, with communication test results showing Good Quality. The system development results demonstrate that the IIoT-based Pneumatic Control System can be controlled and monitored via a smartphone by accessing the Node-Red-based Web HMI